Pengaruh Locus Of Control, Gaya Kepemimpinan, Budaya Organisasi, Serta Pengaruh Pemahaman Good Governance Terhadap Kinerja Auditor(Studi Empiris Pada Kantor Akuntan Publik di Kota Surakarta dan DIY) - Pratiwi, Faridah Husnun, Drs. Suyatmin Waskito Adi, M.Si (2017)
ABSTRACT The purpose of this study was to examine the effect Locus Of Control, Leadership Style, Organization Culture, and Good Governance of the Performance Auditor. Responden in this research were Auditor who work im Publik Accounting firms in Surakarta and DIY. Determination of sample, using a purposive sampling method. The data in this research is obtained by distributing questionnaires to the respondents. The number of respondents as many 50 people. The data analysis was using multiple linear regressions analysis. The results of this research indicate that Locus Of Control have a significant effect on the Performance Auditor, while Leadership Style, Organization Culture, and Good Governance have a not significant effect on the Performance Auditor. Key words : Locus Of Control, Leadership Style, Organization Culture, Good Governance, Performance Auditor.